The effectiveness of edmodo and schoology in descriptive writing for Universitas Muhammadiyah Yogyakarta students - Oktaviani, Rizki Dwi; Widyantoro, Agus (LingTera, 2021)
This research was aimed to figure out (1) the students' achievement in descriptive writing taught by using Edmodo and Schoology, (2) the differences of students' achievement in descriptive writing taught by using Edmodo, Schoology, and the conventional media, and (3) the most effective media among the media compared in descriptive writing for the students of Yogyakarta Muhammadiyah University. This research was a quasi-experiment study with a nonequivalent (pretest and posttest) control group design. The data were collected through written tests. The reliability of the instruments was gained using inter-rater reliability. The data were analyzed using the covariant analysis (ANCOVA) and the Scheffe test. The results of the study showed that: (1) the use of Edmodo and Schoology gave a positive contribution to students' achievement in descriptive writing, (2) there were differences among students' achievement in descriptive writing taught by using Edmodo, Schoology and the conventional media, (3) the use of Edmodo and Schoology was more effective than the conventional media.